2020
DOI: 10.1001/jamapsychiatry.2019.2974
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Proteome Alterations in the Primary Auditory Cortex of Individuals With Schizophrenia

Abstract: IMPORTANCE Findings from unbiased genetic studies have consistently implicated synaptic protein networks in schizophrenia, but the molecular pathologic features within these networks and their contribution to the synaptic and circuit deficits thought to underlie disease symptoms remain unknown.OBJECTIVE To determine whether protein levels are altered within synapses from the primary auditory cortex (A1) of individuals with schizophrenia and, if so, whether these differences are restricted to the synapse or occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 71 publications
1
42
0
Order By: Relevance
“…Using dualantigen immunofluorescence, we also demonstrate co-localization of SR with the PSD marker, PSD-95 in CA1 ( Fig 2D). Finally, mass spectrometry confirmed the presence of SR in synaptosomes (MacDonald et al, 2019) prepared from human hippocampus, along with other well-known pre-and post-synaptic markers (Fig 2E,Extended Data Since we detected the enzyme SR in dendrites and spines, we next examined whether the NMDAR coagonist D-serine is also localized to these compartments. Using immuno-EM and a D-serine immunostaining protocol that we previously validated using SRKO mice (Balu et al, 2014), we observed high numbers of nanogold particles in CA1 s.r.…”
Section: Postsynaptic Localization Of Serine Racemase and D-serinementioning
confidence: 53%
“…Using dualantigen immunofluorescence, we also demonstrate co-localization of SR with the PSD marker, PSD-95 in CA1 ( Fig 2D). Finally, mass spectrometry confirmed the presence of SR in synaptosomes (MacDonald et al, 2019) prepared from human hippocampus, along with other well-known pre-and post-synaptic markers (Fig 2E,Extended Data Since we detected the enzyme SR in dendrites and spines, we next examined whether the NMDAR coagonist D-serine is also localized to these compartments. Using immuno-EM and a D-serine immunostaining protocol that we previously validated using SRKO mice (Balu et al, 2014), we observed high numbers of nanogold particles in CA1 s.r.…”
Section: Postsynaptic Localization Of Serine Racemase and D-serinementioning
confidence: 53%
“…The majority of these studies found no statistically significant effects of either HAL or OLZ on SYN protein levels in the rat hippocampus and frontal cortex 23,[38][39][40] ; one study reported increased SYN levels in cortical lysates upon chronic administration of OLZ, however this study did not use clinically comparable dosing 41 . Supporting the majority of the rat studies, exposure of rhesus monkeys to clinically-comparable levels of HAL for >1 year found no change in SYN, either at DNA or protein levels, in cortical areas relevant to schizophrenia 42,43 . The effect of APD on postsynaptic marker expression has mostly been investigated at the mRNA level, with Homer1a and PSD-95 as the most commonly reported markers.…”
Section: Summary and Interpretation Of Resultsmentioning
confidence: 75%
“…Also increased protein insolubility was found in STG and frontal cortex in schizophrenia [ 29 ]. Recently, reductions in synaptosome levels of post-synaptic excitatory proteins were reported in primary auditory cortex of schizophrenia [ 30 ], consistent with synaptic glutamatergic hypofunction. Hence, this literature converges with our findings to support that left STG abnormalities with early hypoglutamatergic dysfunction may be a trait characteristic of schizophrenia.…”
Section: Discussionmentioning
confidence: 91%